Effects of isokinetic knee muscle training on bone morphogenetic proteins and inflammatory biomarkers in post-traumatic osteoarthritis after anterior cruciate ligament injury: A randomized trial - Gopal Nambi; Walid Kamal Abdelbasset; Saud M. Alrawaili; Tamer E. Elnegamy; Ahmed M. Abodonya; Ayman K. Saleh; Anju Verma (Medical Journals Sweden, 2020)
Objective: To determine the effects of isokinetic training of the knee muscles on bone morphogenetic proteins and inflammatory biomarkers in post-traumatic osteoarthritis after anterior cruciate ligament injury in university football players. Methods: A total of 60 participants with post-traumatic osteoarthritis after anterior cruciate ligament injury were randomly allocated into 3 groups: isokinetic training (n = 20), sensory motor training (n = 20) and control (n = 20) groups. The groups under-went different training programmes for 4 weeks. Clinical and biochemical values were measured at baseline, 4-week, 8-week and 6-month follow-ups. Results: At the end of the 4 week training period the isokinetic group showed more significant changes in pain intensity and functional disability than the sensory motor training or control groups (p < 0.001). There was no significant changes in bone morphogenic protein measures, (e.g. bone morphogenic proteins 2, 4, 6, and 7) in any of the groups. There was positive changes in inflammatory markers (CRP, TNF-α, IL-2, IL-4, IL-6) in the isokinetic training group compared with the other 2 groups (p < 0.001). Conclusion: Isokinetic training results in greater improvements in pain and functional disability than sensory motor training in post-traumatic osteoarthritis after anterior cruciate ligament injury in university football players. The isokinetic training programme had a beneficial effect on levels of inflammatory biomarkers and negligible effect on bone morphogenic proteins.